THE INFLUENCE OF ETHICS AND AUDIT RISK ON AUDIT QUALITY WITH PROFESSIONAL SKEPTICISM AS A MODERATING VARIABLE: A CASE IN PUBLIC ACCOUNTING FIRM (KAP) LOCATED IN SURABAYA - FIDELA LUTHFIANA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The audit quality is a complex issue as it deals with so many interfering factors and depends on the viewpoints of each party. This study uses the statement from De Angelo that good audit quality can be achieved, when the auditor is able to discover and report the existing infringements in the client’s accounting system. Following that, this study is intended to find out the influence of ethics and audit risk on audit quality with professional skepticism as a moderating variable. The respondents of this research are the auditors who work in public accounting firms located in Surabaya. This research uses primary data that were collected by questionnaires. The survey method was chosen as data collection method by delivering questionnaires directly to the respondents. A hundred and six questionnaires were distributed to several public accounting firms and only 87 of them that could be processed. The analytical technique used was Multiple Linear regression and Moderation Testing using residual. The result shows that, first, ethics affects audit quality. Second, audit risk affect audit quality. Third, professional skepticism strengthens effect of ethics on audit quality. Fourth, professional skepticism strengthens effect of audit risk on audit quality. Keywords: audit quality, ethics, audit risk, and professional skepticism.